2017
DOI: 10.1186/s41182-016-0041-6
|View full text |Cite
|
Sign up to set email alerts
|

Temperature during pregnancy influences the fetal growth and birth size

Abstract: BackgroundBirth weight and length have seasonal fluctuations. However, it is uncertain which meteorological element has an effect on birth outcomes and which timing of pregnancy would explain such effect. Therefore, the purpose of this study was to examine temperature effects during pregnancy and which timing of pregnancy has effects on size at birth.MethodsA large, randomized, controlled trial of food and micronutrient supplementation for pregnant women was conducted in Matlab, Bangladesh (MINIMat Study), whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 36 publications
2
51
2
1
Order By: Relevance
“…Changes in birth weight were especially small in studies in low and middle income countries. 48 81 Notably, in the lag measures, high temperatures in the last four weeks of pregnancy appeared to have little impact on birth weight, and were even associated with an increase in birth weight in two studies (supplementary fig 7b). 48 80 Among studies that showed an association between reduced weight and high temperatures, the largest impacts were in women aged less than or equal to 22 or above 40 29 71 79 ; who were black, 79 indigenous, 48 or Hispanic 71 ; and of low socioeconomic status 29 71 79 ( fig 5 , fig 6 , supplementary fig 8a).…”
Section: Resultsmentioning
confidence: 95%
“…Changes in birth weight were especially small in studies in low and middle income countries. 48 81 Notably, in the lag measures, high temperatures in the last four weeks of pregnancy appeared to have little impact on birth weight, and were even associated with an increase in birth weight in two studies (supplementary fig 7b). 48 80 Among studies that showed an association between reduced weight and high temperatures, the largest impacts were in women aged less than or equal to 22 or above 40 29 71 79 ; who were black, 79 indigenous, 48 or Hispanic 71 ; and of low socioeconomic status 29 71 79 ( fig 5 , fig 6 , supplementary fig 8a).…”
Section: Resultsmentioning
confidence: 95%
“…Temperature is associated with length at birth. The neonate born in the colder season was significantly shorter than those born in the summer season (Rashid et al, 2017;Svefors, 2018). Flood is one of the most common natural disasters in Bangladesh.…”
Section: Ta B L Ementioning
confidence: 98%
“…have a partial immunity and are consequently more vulnerable to parasite infection than adults ( Langhorne et al, 2008 ; Cowman et al, 2016 ; Rodriguez-barraquer et al, 2018 ). Studies have demonstrated a high asymptomatic malaria prevalence in this age group ( Nankabirwa et al, 2014 ; Clarke et al, 2008 ; Sultana et al, 2017 ; Nankabirwa et al, 2013 ; Nankabirwa et al, 2015 ; Yeka et al, 2015 ; Ahorlu et al, 2009 ). Conversely, in high transmission areas, children under-five are more at risk of severe malaria due to lack of acquired immunity ( World Health Organization, 2019 ; Langhorne et al, 2008 ; Cowman et al, 2016 ; World Health Organization, n.d. ; Ndungu et al, 2012 ).…”
Section: Discussionmentioning
confidence: 97%
“…A recent systematic review ( van Eijk et al, 2015 ) reported a strong correlation between malaria prevalence in children aged 0–59 months and pregnant women (r:0.87, p < 0.0001), with a higher average prevalence observed in children than in pregnant women (pooled prevalence ratio (PPR):1.44, 95%CI:1.2–1.62). It has also been suggested that children above five and children of school age have a higher asymptomatic malaria parasitaemia prevalence than their under-five counterparts ( Walldorf et al, 2015 ; Nankabirwa et al, 2014 ; Sultana et al, 2017 ). However, a relationship between malaria parasite carriage in pregnant women and school-aged children has not been established.…”
Section: Introductionmentioning
confidence: 99%